EFEKTIVITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK PADA PEMBELAJARAN MATEMATIKA - utami, adisty arisma (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
RealisticÂ MathematicsÂ EducationÂ (PMR)Â isÂ anÂ approachÂ toÂ mathematics educationÂ adoptedÂ fromÂ RealisticÂ MathematicsÂ EducationÂ (RME)Â whichÂ hasÂ been developedÂ inÂ theÂ NetherlandsÂ sinceÂ 1970.Â PMRÂ tendsÂ toÂ provideÂ explanationsÂ relatedÂ to realisticÂ things,Â soÂ that studentsÂ canÂ easilyÂ digestÂ theÂ learningÂ deliveredÂ byÂ educatorsÂ . ThisÂ studyÂ aimsÂ toÂ conductÂ aÂ literatureÂ reviewÂ relatedÂ toÂ theÂ effectivenessÂ ofÂ realistic mathematics education (PMR) in learning mathematics. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection was carried outÂ byÂ documentingÂ andÂ reviewingÂ allÂ articlesÂ relatedÂ toÂ mathematicsÂ educationÂ inÂ the periodÂ 2010 â€“2020.Â TheÂ articlesÂ usedÂ inÂ thisÂ studyÂ wereÂ 30Â accreditedÂ nationalÂ and internationalÂ journalÂ articlesÂ obtainedÂ fromÂ GoogleÂ Schoolar,Â ResearchÂ Gate,Â SINTA, DOAJ,Â andÂ Scopus.Â BasedÂ onÂ thisÂ research,Â itÂ wasÂ foundÂ thatÂ RealisticÂ Mathematics Education (PMR) is able to improve learning outcomes and can improve many students' mathematicalÂ abilities.Â StartingÂ fromÂ theÂ abilityÂ ofÂ intuition,Â mathematicalÂ problem solving ability, connection and communication skills of students. Â Â Keywords: RealisticÂ MathematicsÂ Education,Â MathematicsÂ Learning,Â Systematic literature Review